Perfiles de afrontamiento y su relación con la ansiedad ante exámenes en estudiantes de Psicología - Morel González, Celina Elizabeth (2022)
The relationship between coping responses and test anxiety was addressed by different investigations. However, no studies have been found about coping profiles and their relationship to test anxiety. The objective of this research was to study the coping profiles of 100 psychology students and their relationship with test anxiety. A solution of 3 well differentiated clusters was found regarding the mean scores of coping responses. It was found that the participants belonging to the cluster with the lowest scores in all the coping responses experienced a lower level of concern, emotionality and global test anxiety. The implications of these results are discussed.